A Compact CPW-Fed Curved Meander Line Monopole Antenna (MLMA) for GSM Application - Nor Afifah Borhan; Noor Asniza Murad (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Monopole antenna is widely used in many communication systems especially in broadcasting where omnidirectional pattern allow the 360-degree coverage. However, at low frequency the conventional design may require miniaturization to fit in versatile spaces. Thus, this paper discusses a low cost, compact CPW-fed curved meander line monopole antenna (MLMA) designed to operate at 0.9 GHz GSM band. The overall dimension is 25mm x 80mm. The antenna is well matched at required GSM band with the bandwidth from 0.88 GHz to 0.93 GHz. Comparison between the conventional MLMA and curved (MLMA) is made in term of return loss and gain. It was found that the curved MLMA has a better gain compared to the conventional MLMA which is 1.472 dB.